Synthesis of Copper Doped Nano Crystalline Zinc Oxide - Raja1, K.; Ramesh2, P.S.; Geetha1, D. (Asian Journal of Chemistry, 2013)
Copper doped zinc oxide was prepared by simple solvothermal method of copper(II) nitrate and zinc(II) nitrate hexahydrate, sodium carbonate and sodium hydroxide were used as the precursors in aqueous medium and annealed at 550 ºC for 2 h. The particle size and morphology were tailored by adjusting the reactant molar ratio of copper(II) nitrate, while the reaction temperature and the time remained unchanged. The synthesized samples have been characterized by powder X-ray diffraction; UV visible spectrophotometer and Fourier transformer infrared spectroscopy. The size and morphology of the ZnO micro and nanocrystals were investigated by scanning electron microcopy. The optical properties of ZnO micro and nanocrystals, as well as their dependence on the particle size and morphology. The UV-visible spectra showed that the modification of the particle size and the morphology from nanospheres to microrod resulted in increased absorption, 398 to 403 and a slight green shift of the absorption edge. The presence of functional groups and the chemical bonding is confirmed by FTIR spectra. It is proposed that Cu doping concentration limit is below 0.12 % molar fraction which is supported by the detailed XRD analysis and the derived structural parameters. The calculated crystalline size decreases from 24 nm to 12 nm for x = 0 to 0.3 then reaches 24 nm for x = 0.12 % which is confirmed by SEM micrographs.